Revisiting the Causal link Between Agriculture, Industrial output and Financial Sector Development in South Africa - Sibanda, Mabutho; Gumede, Zamanguni; Nomlala, Bomi; Mkhize, Msizi; Ndlela, Hlengiwe (Journal of Reviews on Global Economics, 2019)
This study seeks to establish the relationship between agriculture, industrial output and financial sector development in South Africa. It uses the Autoregressive Distributed Lag, Error Correction models and Granger causality techniques to test for long- and short-run relationships. The evidence from the models indicates the presence of a long-run relationship between industrial output and agriculture, which suggests that these sectors depend on each other for raw materials and inputs. In addition, stock market development represented by market capitalization has a long-run relationship with agriculture. However, no long-run relationship is established between credit extension and agriculture; and between gross fixed capital formation and agriculture, suggesting that an increase in agricultural output does not impact investment in long-term fixed assets. The evidence also shows a long-run relationship between exports and agricultural output, which is consistent with the export-led growth hypothesis. These findings have implications for policy formulation and allocation of resources.